Evaluasi Ancaman Baru Dalam Keamanan Informasi: Systematic Literature Review Tentang Kerentanan Cyber Security Pasca-Pandemi : Evaluating Emerging Threats In Information Security: A Systematic Literature Review On Post-Pandemic Cybersecurity Vulnerabilities - Karunia, Wilis Arum; Zahra, Awanda Fitya; Amrozi, Yusuf (Cyber Security dan Forensik Digital, 2025)
Pandemi COVID-19 telah mempercepat transformasi digital di berbagai sektor, yang disertai dengan peningkatan risiko dan ancaman keamanan siber. Penelitian ini menggunakan pendekatan Systematic Literature Review (SLR) untuk mengidentifikasi ancaman keamanan siber yang muncul selama pandemi serta strategi mitigasi yang telah diterapkan. Hasil penelitian menunjukkan bahwa serangan seperti phishing, malware, ransomware, dan serangan DDoS meningkat signifikan, dengan sektor kesehatan dan keuangan menjadi target utama. Selain itu, faktor manusia, seperti stres kerja jarak jauh dan kurangnya pelatihan keamanan, turut berkontribusi pada kerentanan sistem. Strategi mitigasi yang terbukti efektif mencakup implementasi autentikasi multi-faktor (MFA), enkripsi data, pelatihan kesadaran keamanan, dan pemantauan real-time. Namun, transformasi digital yang dilakukan secara terburu-buru tanpa perencanaan keamanan menjadi tantangan utama yang harus diatasi. Penelitian ini memberikan wawasan penting bagi organisasi untuk meningkatkan ketahanan siber melalui integrasi teknologi, kebijakan keamanan, dan pelatihan karyawan yang berkelanjutan. Implikasi dari penelitian ini diharapkan dapat membantu pengembangan strategi keamanan siber yang lebih tangguh untuk menghadapi tantangan di masa depan. Kata kunci: keamanan siber, pandemi covid-19, ancaman siber, mitigasi, transformasi digital, pelatihan keamanan ------------------------ Abstract The COVID-19 pandemic has accelerated digital transformation across various sectors, accompanied by increased risks and cybersecurity threats. This study aims to identify cybersecurity threats that emerged during the pandemic and evaluate the mitigation strategies that have been implemented, using a Systematic Literature Review (SLR) approach. The research identified 53 articles during the initial search phase. Subsequently, a preliminary analysis was conducted by reviewing the titles and abstracts to assess the relevance of the articles, narrowing the selection to 21 articles. At the final stage, an in-depth evaluation was performed to ensure the quality and relevance of the articles to the research focus, resulting in 12 articles being selected for the literature review. The findings reveal a significant increase in attacks such as phishing, malware, ransomware, and DDoS, with the healthcare and financial sectors being primary targets. Additionally, human factors, such as stress from remote work and a lack of security training, contributed to system vulnerabilities. Effective mitigation strategies included the implementation of multi-factor authentication (MFA), data encryption, security awareness training, and real-time monitoring. However, the rapid digital transformation carried out without proper security planning posed a major challenge that needs to be addressed. This research provides valuable insights for organizations to enhance cyber resilience through the integration of technology, security policies, and continuous employee training. The implications of this study are expected to aid in the development of more robust cybersecurity strategies to address future challenges. Keywords: cybersecurity, covid-19 pandemic, cyber threats, mitigation, digital transformation, security training